2017
DOI: 10.1177/2397847317741884
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the microbiome in health and disease

Abstract: The analysis of human microbiome is an exciting and rapidly expanding field of research. In the past decade, the biological relevance of the microbiome for human health has become evident. Microbiome comprises a complex collection of microorganisms, with their genes and metabolites, colonizing different body niches. It is now well known that the microbiome interacts with its host, assisting in the bioconversion of nutrients and detoxification, supporting immunity, protecting against pathogenic microbes, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 423 publications
(524 reference statements)
0
52
0
Order By: Relevance
“…[ 1 ] The number of microbes present in our bodies is almost the same or even more as compared to that of our cells. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The number of microbes present in our bodies is almost the same or even more as compared to that of our cells. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Murtaza et al [ 15 ] reported that a KD elicited significant decreases in relative concentrations of Faecalibacterium spp. and Bifidobacterium spp., both of which have been reported as being beneficial for maintaining intestinal homeostasis [ 32 ]. Faecalibacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The findings outlined in this study indicate that elevated selective pressure on the gut microbiota is observed among individuals who adhere to a KD when compared with those who consume high or periodized carbohydrate diets [ 15 ]. Studies have highlighted the potential consequences of alteration to the gut microbiome such as the development of digestive pathologies, metabolic diseases, neurological disorders, cancers, immune conditions, and skin problems [ 32 ]. Additionally, this particular study also demonstrated the negative associations between abundances of Dorea spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the composition and stability of the mucus layer represents a critical aspect in preventing direct contact between the host and potentially pathogenic bacteria. Of note, each of these components is affected by the inflammatory processes as well as by CS exposure 14 . Both genetic and chemically induced IBD mouse models have been used to elucidate the molecular mechanisms behind CS-IBD interaction.…”
Section: Exposure To Cigarette Smoke (Cs) Causes Detrimental Health Ementioning
confidence: 99%